Raising Thalictrum uncatum var. angustialatum (Ranunculaceae) from China to T. angustialatum as an independent species based on evidence from morphology, geographical distribution, cytology and molecular systematics - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Critical observations on living plants in the wild revealed remarkable differences in floral and achene characters between Thalictrum uncatum var. angustialatum (Ranunculaceae) and its type variety, T. uncatum var. uncatum, both from China. Their geographical distributions are basically independent, only slightly overlapping in western Sichuan and northwestern Yunnan. Moreover, T. uncatum var. angustialatum was found to be a tetraploid with the chromosome number of 2n = 4x = 28, whereas T. uncatum var. uncatum a diploid with 2n = 2x = 14. Furthermore, molecular phylogenetic analyses indicated that T. uncatum var. angustialatum was more closely related to T. sinomacrostigma, also a tetraploid, than to T. uncatum var. uncatum. Evidence from morphology, geographical distribution, cytology and molecular systematics, therefore, all indicates that T. uncatum var. angustialatum may better be raised to the specific rank as an independent species of its own, i.e. T. angustialatum. A full description is provided for T. angustialatum.